2020
DOI: 10.2147/ott.s205950
|View full text |Cite
|
Sign up to set email alerts
|

<p>Immunotherapy For Ovarian Cancer: Recent Advances And Combination Therapeutic Approaches</p>

Abstract: Epithelial ovarian cancer (EOC) is the most lethal gynaecological cancer. Although many advances have been made in therapeutic strategies, the global standard of care still remains radical surgery plus chemotherapy, but new scenarios need to be explored to improve survival. The role of immunotherapy in EOC treatment is controversial. Results obtained from studies evaluating immunotherapy are contradictory: in particular data on survival are not as good as expected when immunotherapy was administered alone, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 95 publications
1
49
0
2
Order By: Relevance
“…Furthermore, FCGBP was predicted to be involved in chemokine signaling pathways, as well as the innate and adaptive immune systems. Moreover, considering that the infiltration of immune cells (especially macrophages) is important for the overall survival of patients with ovarian cancer [ 8 , 9 ], we examined the association between FCGBP expression and the immune cell infiltration level and found that M2 macrophage infiltration increased, while M1 macrophage infiltration decreased in tissues with high FCGBP expression. Our results suggest potential functional role of FCGBP in ovarian cancer, thereby highlighting a mechanistic basis whereby FCGBP influences M2 macrophage polarization in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FCGBP was predicted to be involved in chemokine signaling pathways, as well as the innate and adaptive immune systems. Moreover, considering that the infiltration of immune cells (especially macrophages) is important for the overall survival of patients with ovarian cancer [ 8 , 9 ], we examined the association between FCGBP expression and the immune cell infiltration level and found that M2 macrophage infiltration increased, while M1 macrophage infiltration decreased in tissues with high FCGBP expression. Our results suggest potential functional role of FCGBP in ovarian cancer, thereby highlighting a mechanistic basis whereby FCGBP influences M2 macrophage polarization in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, single-agent Abs against CTLA-4, PD-1 or PD-L1 revealed modest results in epithelial ovarian cancer with median response rates (RR) less than 15% and a control of disease rate less than 50% [ 25 , 26 ]. On the contrary, combinations of immunotherapy with chemotherapy, anti-angiogenic agents or poly (ADP-ribose) polymerase (PARP) inhibitors have shown promising results in terms of ORR and median PFS [ 27 ]. However, monotherapy with pembrolizumab in women with MSI-high tumors seems to be a reasonable therapeutic option irrespective of the tumor location as it has already been mentioned above [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TMB of NSCLC is $10-fold that of ovarian cancer [22]. In fact, clinical studies of ICBs indicated NSCLC rather than ovarian cancer was the preferred target [23,24]. These findings suggest that preexisting immunity levels are higher in patients with NSCLC than in patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%